Development of mucoadhesive biopolymers for food formulation - Mohd Faizal, Ali (2015)
Development of mucoadhesive biopolymer has received great attention in the pharmaceutical application due to its ability to retain the drug dosage at the specific targeted area. This special property could be applied in food formulation for optimum delivery of the active ingredients in the mouth. This research was carried out to study, correlate and review several in vitro analytical methods that can be used in development process for characterisation of mucoadhesive polymer. Four well known mucoadhesive biopolymers namely, chitosan, pectin, sodium alginate and sodium carboxymethylcellulose (CMC) were used in this study. A modified rheological characterisation was used to study the interaction between the biopolymers with mucin and the assessment was based on the viscosity synergism. The detachment force characterisation was carried out via pull-off and tensile test using texture analyser and atomic force microscopy (AFM). Kinetic interaction study was done using quartz crystal microbalance with dissipation monitoring (QCMD) and interpretation of data from the modified rheological characterisation. Meanwhile, the removal of biopolymer emulsion after water flushing in a flow cell was observed under a microscope. It was found that mucoadhesion properties of tested biopolymers were affected by the concentration of biopolymer solutions, molecular weight, contact time, ionic strength and pH. Sodium alginate was characterised as the most mucoadhesive material by all the methods while QCMD shows CMC has the highest interaction with mucin layer compared to sodium alginate and pectin.